Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils. Issue 23 (2nd December 2022) - Kopittke, Peter M.; Berhe, Asmeret Asefaw; Carrillo, Yolima; Cavagnaro, Timothy R.; Chen, Deli; Chen, Qing-Lin; Román Dobarco, Mercedes; Dijkstra, Feike A.; Field, Damien J.; Grundy, Michael J.; He, Ji-Zheng; Hoyle, Frances C.; et al.
Abstract: Not only do soils provide 98.7% of the calories consumed by humans, they also provide numerous other functions upon which planetary survivability closely depends. However, our continuously increasing focus on soils for biomass provision (food, fiber, and energy) through intensive agriculture is rapidly degrading soils and diminishing their capacity to deliver other vital functions. These tradeoffs in soil functionality – the increased provision of one function at the expense of other critical planetary functions – are the focus of this review. We examine how land-use change for biomass provision has decreased the ability of soils to regulate the carbon pool and thereby contribute profoundly to climate change, to cycle the nutrients that sustain plant growth and ecosystem health, to protect the soil biodiversity upon which many other functions depend, and to cycle the Earth's freshwater supplies. We also examine how this decreasing ability of soil to provide these other functions can be halted and reversed. Despite the complexity and the interconnectedness of soil functions, we show that soil organic carbon plays a central role and is a master indicator for soil functioning and that we require a better understanding of the factors controlling the behavior and persistence of C in soils. Given the threats facing humanity and their economies, it is imperative that we recognize that Soil Security is itself an existential challenge and that we need to increase our focus on the multiple functions of soils for long-term human welfare and survivability of the planet. Graphical abstract: UF0001